2008
DOI: 10.2214/ajr.07.2888
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-Guided Percutaneous Needle Aspiration or Catheter Drainage of Neonatal Liver Abscesses: 14-Year Experience

Abstract: Neonatal liver abscess is associated with good long-term outcome and minimal complications when imaging-guided percutaneous aspiration or drainage is performed in conjunction with long-term antibiotic coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“…PCD was performed in 18 cases and was successful in 16/18 (88.8%), whereas two of these cases required surgery. There is scanty data regarding safety and effectiveness of PCD in children [18]. In a randomized controlled trial comparing aspiration and catheter drainage in adults with LA, Rajak et al [28] found PCD to be more effective than PNA (success rate 100% vs. 60%; p<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCD was performed in 18 cases and was successful in 16/18 (88.8%), whereas two of these cases required surgery. There is scanty data regarding safety and effectiveness of PCD in children [18]. In a randomized controlled trial comparing aspiration and catheter drainage in adults with LA, Rajak et al [28] found PCD to be more effective than PNA (success rate 100% vs. 60%; p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited amount of data on the pediatric population, mostly in the form of case reports on percutaneous catheter drainage (PCD) [18,19,32].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention has the advantage of thorough exploration of the abdomen and extirpation of known or unsuspected primary foci of infection that might not have been detected in imaging. [13][14][15] We recommend trans peritoneal surgical drainage to allow abdominal exploration and thorough exploration of the liver for multiple hepatic abscesses, although laparoscopic drainage has shown excellent result in some patients. From our series it is difficult to evaluate which type of drain is best.…”
Section: -12mentioning
confidence: 99%
“…Needle aspiration appears to be safe and effective [10] if used in conjunction with appropriate antibiotics provided a rapid response is obtained as is illustrated by this series. This study does not support the suggestion that early drainage speeds up resolution, limits the length of intravenous antibiotic course as 50% responded to antibiotic therapy alone.…”
Section: Discussionmentioning
confidence: 75%